Contraception History and Nutritional Status Affected the Menopause Incidents on Women - Indah Yun Diniaty Rosidi; Mutmainna Kamaruddin (Journal of Ners and Midwifery, 2023)
Menopause is a natural process that every woman will experience. Menopause is the end of a woman's reproductive period or the time her last menstrual cycle occurs. The active reproductive period is marked by the first menstruation or what is usually called menarche. The diagnosis of menopause is made after amenorrhea for at least one year. Cessation of menstruation may be preceded by a longer menstrual cycle with less bleeding. The type of research was analytical observational or analytical survey with a retrospective cohort approach. This research was conducted at the Bara-Baraya Community Health Center, Makassar City, South Sulawesi The samples in this study were women who had gone through menopause, were able to speak Indonesian, were not seriously ill (such as a stroke) and were not impaired by their sense of sight and hearing (such as blindness or deafness). This research used 47 respondents taken by purposive sampling technique. The data analysis used the multiple linear regression test. The results of this study showed there was an effect of contraceptive history and nutritional status on the incidence of menopause in women. Therefore, it is hoped that there will be a program for health workers around menopause for women.